Optimization of Velocity Flap Structures in High Sensitivity Macrofluidic Airflow Sensor - Dzulhelmy bin Amari, Mohamad; Saifuddin b. Abdull Shukor, Muhamad; Che Abdullah, Sukarnur (International Journal of Engineering and Technology, 2018)
Automated reaction from the system is most important in fulfilling the requirement of the intelligent control system. Hence, many related studies regarding in developing the hardware of the system such as high sensitivity of the airflow sensor in detecting the changes either in user or the environment. The effect of the fast detection of the sensor through the high sensitivity of the airflow sensor have enable the system to identify and analyze the behavior of the user in higher accuracy compared to conventional system. Within the scope of airflow sensitivity, separation between two parts in the airflow sensor in altering the velocity impact have been inquired in purpose, while a few investigations in relations to determine the pressure contour of the main parts have been explored by application of using Computational Fluid Dynamics (CFD. This simulation is performed in the ANSYS program software. Thus, this study consequently intends to be focus on detection the high sensitivity of the airflow movement by distinguishing the high and low velocity impact. The optimization the airflow sensor in this study based on design parameter also done in order to design and develop a highly sensitive airflow sensorÂ Â Â